1993
DOI: 10.1111/j.1600-0765.1993.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein, albumin and cystatin concentrations in saliva of healthy subjects and of patients with gingivitis periodonitis

Abstract: Salivary protein, albumin and cystatin concentrations were investigated in subjects with a healthy periodontium and in patients with gingivitis or periodontitis. Protein and albumin concentrations in saliva of individuals with gingivitis or periodontitis were significantly increased compared with healthy subjects. Salivary protein and albumin appeared to be positively correlated in all the groups, which suggests that the increase in salivary protein concentration in subjects with gingivitis or periodontitis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
2
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 28 publications
10
80
2
3
Order By: Relevance
“…Increases in salivary albumin have also been shown in patients with a variety of medical conditions and with advancing age [10]. Several studies have shown patients with PD to have worse oral health compared with controls [11] and therefore the increases in salivary protein and DJ--1 concentration among patients with PD reported here may be due to worse oral health, reduced mucosal integrity and an increased leakage of serum proteins into the saliva, rather than as a direct result of the Parkinson's disease process itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in salivary albumin have also been shown in patients with a variety of medical conditions and with advancing age [10]. Several studies have shown patients with PD to have worse oral health compared with controls [11] and therefore the increases in salivary protein and DJ--1 concentration among patients with PD reported here may be due to worse oral health, reduced mucosal integrity and an increased leakage of serum proteins into the saliva, rather than as a direct result of the Parkinson's disease process itself.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafiltration of serum is believed to be the main mechanism through which albumin enters the oral cavity and its salivary concentration has therefore been proposed to reflect compromised mucosal integrity and periodontal disease [10]. Increases in salivary albumin have also been shown in patients with a variety of medical conditions and with advancing age [10].…”
Section: Discussionmentioning
confidence: 99%
“…The values were expected to be significantly much lower in periodontally healthy individuals than in those with gingival inflammation and/or periodontitis. 49 Parasitemia was estimated from thin films of venous blood following staining with Giemsa and reticulocyte counts made from stained blood smears (0.3% [v/v] brilliant cresyl blue in methanol).…”
Section: Methodsmentioning
confidence: 99%
“…There was not any difference in the concentration of salivary albumin depending on pregnancy, as the same levels were measured in pregnant and non-pregnant women (Selby, 1988). Salivary albumin concentration in subjects with gingivitis or perodontitis is caused by leakage of plasma proteins (Henskens, 1993). The increase in the concentration of albumin in whole saliva was always detected prior to the clinical appearance of stomatitis, suggesting that albumin in whole saliva may be a marker and predictor of this complication.…”
Section: Wwwintechopencommentioning
confidence: 68%